1997
DOI: 10.1016/s0092-8674(00)81865-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Melanocortin-4 Receptor Results in Obesity in Mice

Abstract: The melanocortin-4 receptor (MC4-R) is a G protein-coupled, seven-transmembrane receptor expressed in the brain. Inactivation of this receptor by gene targeting results in mice that develop a maturity onset obesity syndrome associated with hyperphagia, hyperinsulinemia, and hyperglycemia. This syndrome recapitulates several of the characteristic features of the agouti obesity syndrome, which results from ectopic expression of agouti protein, a pigmentation factor normally expressed in the skin. Our data identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

91
1,991
5
34

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,796 publications
(2,121 citation statements)
references
References 79 publications
91
1,991
5
34
Order By: Relevance
“…Although both MC3-and MC4-Rs are abundant in the hypothalamus [47,52], it remains unclear which receptor is the key regulator of energy balance. The obesity phenotype of the MC4-R null mouse strongly supports a role for this receptor in obese states [28]. Transgenic mice lacking the MC3-R have not clarified the role of the MC3-R to the same extent [7,13].…”
Section: The Melanocortin System and The Hpt Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Although both MC3-and MC4-Rs are abundant in the hypothalamus [47,52], it remains unclear which receptor is the key regulator of energy balance. The obesity phenotype of the MC4-R null mouse strongly supports a role for this receptor in obese states [28]. Transgenic mice lacking the MC3-R have not clarified the role of the MC3-R to the same extent [7,13].…”
Section: The Melanocortin System and The Hpt Axismentioning
confidence: 99%
“…However, to date, detailed analyses of the HPT axis in these models are limited. MC3-R deficient mice have normal plasma T4 levels [7,13], although plasma thyroid hormones in either MC4-R-null [28] or AgRP overexpressing [23,50] have not been described. In a recent study, transgenic mice lacking all POMC-derived peptides had reduced plasma T4 [11], consistent with a stimulatory effect of POMC-derived peptides such as α-MSH on the HPT axis.…”
Section: The Hpt Axis In Models Of An Abnormal Melanocortin Systemmentioning
confidence: 99%
“…More recently, the application of pharmacological studies and molecular biology techniques has identified α-MSH as an important hypothalamic satiety signal [11,28]. The MC3R is expressed in both central and peripheral tissues and although the physiological role for this MCR has not yet been identified, it is the MCR with the greatest affinity for γ-MSH and it appears to mediate some aspects of the central control of blood pressure [32].…”
Section: Introductionmentioning
confidence: 99%
“…35,79,80 The MC4-R is an established regulator of food intake and body weight, and blockade of this receptor causes obesity. 77,78 An overeating/obesity syndrome is produced, for example, by targeted deletion of the MC4-R 81 and by mutations in the human MC4-R. [82][83][84][85][86][87][88] The importance of MC4-Rs in humans is highlighted by an estimate that 3-5% of the population suffering from morbid obesity may result from MC4-R mutations. 89 Another important piece of data supporting this model is that POMC-deficient mice and humans display similar obesity phenotypes.…”
mentioning
confidence: 99%